Membangun Harmonisasi di Tengah Masyarakat Majemuk: (Studi Kasus Toleransi Umat Islam dengan Budha di Kudus) - Putri, Maulidia Cahayaning; Tsalits Khoirun Nisa; Riska Aprey Vitasari (Jurnal Studi Agama, 2024)
Indonesian society consists of various tribes, languages, religions, and cultures. Likewise, what happened in Kutuk Village, they lived side by side in the midst of religious differences. The purpose of this study will see how the Kutuk community is diverse but always harmonious and respectful of each other. This study used a qualitative approach with data collection techniques through observation and interviews with religious and community leaders from different religions. The result of this study is to build harmony between communities of the two religions through social activities carried out together. In addition, they also obtained harmony from interfaith marriages that occurred in Kutuk Village.